Kreuzlingen 1963: «Una storia di comunità, in cui poteva accadere di tutto» - Masini, Andrea (Il sogno della farfalla, 2025)
In 1963, Massimo Fagioli worked, together with Lucilla Vendrame, in the therapeutic community founded by Fabrizio Napolitani at the Bellevue Clinic of Ludwig Binswanger, which primarily hosted psychotic patients. This experience, already known through Fagioli’s own accounts shared on multiple occasions, has recently been illuminated by new archival sources, particularly from the psychiatrist’s personal archive. The aim of this article is to provide a comprehensive account of that experience, highlighting its significance in Fagioli’s formation and career, and in his research on psychiatry as psychotherapy.